Estenosis gastro-duodeno yeyunal alta por hematoma traumático de yeyuno.: A propósito de un caso - Barozzi, Carlos; Fleitas, Gabriela; Ruso, Luis; Fernández, Gonzalo; Harretche, Martín (Cirugía del Uruguay, 1996)
There is a 4-12% íncídence of duodeno-jejuno-íleal lesíons in closed trauma of the abdomen. A case is presented of a hematoma of the 2nd jejunal ansa due to closed trauma of the abdomen whose symptoms corresponded to a syndrome of gastro-duodeno-jejunal stenosis. Lesiona/ mechanisms are analysed; the action of a tangentia/ force in the production of this type of submucous /esíons is poínted out. Clinical signs are ínespecífíc wíth asymptomatic períods which make early diagnosis diffícult. Surgical tactíc consísts of resection and anastomosis of the segment involved, avoiding poorly vascularízed areas of the first jejunal ansa and distal íleon. Seríousness in these cases is determined by nutrítíonal and metabolíc effects but prognosis depends on assocíated lesíons.